Melatonin Mitigates Chilling-Induced Oxidative Stress and Photosynthesis Inhibition in Tomato Plants - Meiling Wang; Shuoxin Zhang; Fei Ding (MDPI AG, 2020)
Melatonin has been demonstrated to play a variety of roles in plants. Of particular importance is its role as a potent antioxidative agent. In the present study, we generated melatonin-deficient tomato plants using virus-induced gene silencing (VIGS) approach and melatonin-rich tomato plants by foliar application of melatonin. These tomato plants were used to assess the effect of melatonin on chilling-induced oxidative stress and chilling-induced photosynthesis inhibition. We found that melatonin deficiency increased accumulation of reactive oxygen species (ROS) and aggravated lipid peroxidation in chilling-stressed tomato leaves, while exogenous application of melatonin had the opposite effect. Under chilling stress, melatonin-deficient tomato plants showed impaired antioxidant capacity as evidenced by lower activities of antioxidant enzymes and decreased rations of reduced glutathione (GSH)/oxidized glutathione (GSSG) and reduced ascorbate (AsA)/oxidized ascorbate (DHA), compared with melatonin-rich tomato plants. Furthermore, suppression of melatonin biosynthesis led to more photosynthesis inhibition under the chilling condition and compromised the capability of subsequent photosynthesis recovery in tomato plants. In addition, melatonin-deficient tomato plants displayed less activity of an important Calvin-Benson cycle enzyme sedoheptulose-1,7-bisphosphatase (SBPase) than melatonin-rich tomato plants under chilling stress. Collectively, our data indicate that melatonin is critical for antioxidant capacity and redox balance and is in favor of photosynthesis in tomato plants under chilling stress.